Update on Familial Adenomatous Polyposis-Associated Desmoid Tumors - Yang, Wanjun; Ding, Pei-Rong (Clinics in Colon and Rectal Surgery, 2023)
Desmoid tumors (DT) represent the second high risk of tumor in familial adenomatous polyposis (FAP) patients. Although FAP-associated DTs (FAP-DT) are caused by germline mutations in the adenomatous polyposis coli (APC) gene, extracolonic manifestations, sex, family history, genotype, and the ileal pouch anal anastomosis procedure are all linked to the development of DTs in FAP patients. Multidisciplinary management has replaced aggressive surgery as the preferred treatment of DTs. There is growing evidence to support the use of active surveillance strategy as first-line treatment for FAP-DT patients. Radiotherapy for intra-abdominal desmoids is now rarely used because of severe late toxicity. Pharmacotherapy, however, represents a promising future with the improvement of traditional cytotoxic drugs and the investigation of targeted drugs. Although nonsurgery treatment has been used widely nowadays, surgery remains the mainstay when symptomatic or life-threatening DTs are present. Further research will be needed for more optimal clinical practice.
Keywords: desmoid tumors; familial adenomatous polyposis; APC; treatment